HIRED COMPANIES IN THE PERCEPTION OF GOVERNMENT ACTORS AND HUMANISTS OF ITALY IN XIV-XVI CENTURIES - M. O. Semikov (Гуманитарные и юридические исследования)
Military companies of mercenaries often proved their effectiveness in battle, allowing the ruler who called them to successfully resist external enemies and cope with opposition forces within the city-state. At the same time, military mercenarism gave rise to many new problems: low loyalty to the employer due to low personal interest, threats to the security of the lands in which they were hired, the presence of political ambitions of the leaders of mercenary detachments who were able to organize a coup d’etat and seize power. The intensive displacement of the city militia by detachments of condottieri in many respects instilled anxiety among statesmen and humanists, but the outstanding Italian thinker Niccolo Machiavelli became the main «denouncer» of all the shortcomings of military mercenarism, concerned that mercenaries were the force that could destroy the communal community and the republican order: every condottiere pursued primarily his own interests, in contrast to the citizens of the city-state, who were ready to give their lives for their land.At the same time, Niccolo Machiavelli described for his patron the many forms that mercenary units can turn into. He recalls in the form of peculiar parables what happened in the history of Greece and its individual cities, drawing attention to the present time. Describing mercenary troops and their treachery, he gives examples not only in his native Florence, but also refers to the experience of the entire Apennine peninsula.According to him, all major cities of the state and duchies have suffered to some extent from the actions of mercenaries. And even the most loyal and eminent of them first of all looked for valor for themselves, and tried to get new privileges in the form of loyalty to lands or even a title. Florence was lucky with her mercenaries, or their goals temporarily coincided with the goals of the city-state.Separately, he singles out a completely unusual moment, like the formation of a condottiere a duke due to a successful marriage and military prowess on the example of Francesco Sforza, who gave rise to the Sfoza dynasty, which ruled Milan for many generations, but warns his master about the changeability of fortune.However, the point of view of the Italian humanist reflected the inconsistency of the prevailing realities, with all the dangers of mercenaryism, the Italian states could no longer do without it.